ANALISIS DAYA DUKUNG LAHAN PERTANIAN - Vicky R. B. Moniaga (AGRI-SOSIOEKONOMI, 2011)
Analysis of the carrying capacity of agricultural land is an analysis to determine the carrying capacityof land to the caloric needs of the population. Analysis of the carrying capacity of agricultural land canalso find out whether an area has or has not food self-sufficiency based on caloric needs of the population.The implication of this analysis is that it can find the optimal population that can be supported by existingagricultural land. From this analysis it can be seen that the area of crops and agricultural productivity aretwo factors that can increase the carrying capacity of agricultural land.